THE IMPORTANCE OF THE LEARNER-CENTERED NEUROPSYCHOPEDAGOGICAL ASSESSMENT FOR PEOPLE WITH AUTISM SPECTRUM DISORDER (ASD) - Ruz Freire de Jesus, Amanda; Francisco de Jesus, Ernane (Revista Gênero e Interdisciplinaridade, 2023)
This article proposes to create bases for reflection regarding the neuropsychopedagogical assessment of children and adults who are within the autistic spectrum (ASD). By understanding that Clinical Nepsychopedagogy observes and studies the development of Executive Functions (EF), and seeks to understand with neurobiological bases, how each learner develops, and their challenges, difficulties and potential for full learning, through stimulation and intervention. With this, within this broad spectrum, to outline evaluation strategies, not with the intention of providing a diagnosis (since this should be carried out in detail and often with a multidisciplinary team), but rather to seek to understand areas of interest, skills and difficulties of the learner, so that it is possible to draw up an efficient plan that meets the person who is within the spectrum, for their development. This article was developed through bibliographic research and scientific archives, consultation of books on autism, and the Scientific ElectronicLibrary On Line – SCIELO database.